2016
DOI: 10.1002/ajpa.23026
|View full text |Cite
|
Sign up to set email alerts
|

Comparing primate crania: The importance of fossils

Abstract: The morphospace outlined by living primates largely includes that occupied by fossil taxa, suggesting that the cranial diversity of living primates generally encompasses the total diversity that has evolved in this Order. The evolution of the anthropoid cranium was a significant event allowing anthropoids to achieve significantly greater cranial diversity compared to strepsirrhines. Fossil taxa fill in notable gaps within and between clades, highlighting their transitional nature and eliminating the appearance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
3
6
0
Order By: Relevance
“…Halenar et al () explored cranial shape variation in extant and fossil platyrrhines and showed that several fossil specimens, including Cartelles , do not overlap with the distributions of extant atelid genera, but occupy a unique position in shape space, intermediate between Alouatta and the rest of the family. Similar results were found for Cartelles by Fleagle et al () using a comparative sample expanded to all primates. This suggests that the overall anatomy, and hence probably the niche occupied by Cartelles , have no equivalent among extant platyrrhine primates.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Halenar et al () explored cranial shape variation in extant and fossil platyrrhines and showed that several fossil specimens, including Cartelles , do not overlap with the distributions of extant atelid genera, but occupy a unique position in shape space, intermediate between Alouatta and the rest of the family. Similar results were found for Cartelles by Fleagle et al () using a comparative sample expanded to all primates. This suggests that the overall anatomy, and hence probably the niche occupied by Cartelles , have no equivalent among extant platyrrhine primates.…”
Section: Discussionsupporting
confidence: 88%
“…The pattern of variation seen in the extant atelid species for cranial and endocranial shape, form, CAC and RSC is similar to the variation observed in previous studies on the cranium alone, showing a large difference between Alouatta and the other atelid genera (Aristide, dos Reis, et al, ; Fleagle et al, ; Halenar et al, ; Perez et al, ). Regarding the fossil species, we show that whereas Caipora bambuiorum is within the observed range of variation of extant Brachyteles , Cartelles coimbrafilhoi occupies a region of endocranial form and endocranial shape space that does not overlap with the range of variation seen in any of the extant taxa.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations